Protection of Persons with Disabilities During Armed Conflicts - Saad Mansour , Researcher. Umm Al-Baneen; Jabbar Creedy Al-Qadi , Prof. Dr. Ali (Basra studies journal, 2023)
In the world, there are approximately one billion people with disabilities, constituting about 15% of the global population. They are considered one of the vulnerable groups in the international community. Therefore, there is a recognized need for the international protection of this category both in peacetime in general and during armed conflicts in particular, similar to the protection afforded to non-disabled individuals. The Geneva Conventions of 1949 and their Additional Protocols of 1977, applicable during armed conflicts to all victims, whether international or internal, outline various ways and commitments imposed on the parties involved at those times to protect persons with disabilities, whether indirectly or explicitly. International humanitarian organizations play a significant role in reporting on the situation of people with disabilities during armed conflicts. These are crucial aspects covered in our study, which includes defining armed conflicts and their types, examining the relationship between armed conflicts and persons with disabilities concerning the role of international humanitarian law in their protection, and outlining the obligations imposed by international humanitarian law on conflict parties to safeguard them. Additionally, the research explores the role of humanitarian organizations in protecting persons with disabilities, including the United Nations, its agencies, and humanitarian organizations in collecting and analyzing data related to people with disabilities during armed conflicts, and the right of persons with disabilities to participate in humanitarian assistance operations.